Jumper [videorecording (DVD)] - Liman, Doug; Christensen, Hayden, 1981-; Jackson, Samuel L.; Lane, Diane; Bell, Jamie, 1986-; Bilson, Rachel; Gould, Steven (20th Century Fox Home Entertainment, 2008)
David is a Jumper who can teleport himself anywhere in the world, which creates a fun and exciting life. Things turn deadly when David finds himself pursued by a secret organization sworn to kill Jumpers. He forms an uneasy alliance with another Jumper and becomes a player in a war that has been raging for thousands of years.